Charting nearby stellar systems: the intensity of Galactic cosmic rays for a sample of solar-type stars. Issue 4 (2nd October 2021) - Rodgers-Lee, D; Vidotto, A A; Mesquita, A L
ABSTRACT: Cosmic rays can penetrate planetary atmospheres driving the formation of prebiotic molecules, which are important for the origin of life. We calculate the Galactic cosmic ray fluxes in the habitable zone (HZ) of five nearby, well-studied solar-type stars and at the orbits of two known exoplanets. We model the propagation of Galactic cosmic rays through the stellar winds using a combined 1.5D stellar wind and 1D cosmic ray transport model. We find that the HZ of 61 Cyg A has comparable Galactic cosmic ray fluxes to present-day Earth values. For the other four systems (ϵ Eri, ϵ Ind, ξ Boo B, and π 1 UMa), the fluxes are orders of magnitude smaller than Earth values. Thus, it is unlikely that any as-of-yet undetected Earth-like planets in their HZs would receive a higher radiation dose than is received on Earth. ε Ind b, a Jupiter-like planet orbiting at ∼11 au, receives higher Galactic cosmic ray fluxes than Earth. We find the suppression of Galactic cosmic rays is influenced by whether diffusion or advection dominates at GeV energies and at distances where the wind has reached its' terminal velocity. For advectively dominated winds (∼younger systems), varying the astrospheric size influences the suppression significantly. For diffusion-dominated systems (∼older systems), the astrospheric size, and therefore knowledge of the interstellar medium properties, are not very important. This reduces the Galactic cosmic ray flux uncertainties in the HZ for diffusion-dominated systems. Whether a system is advection- or diffusion-dominated can be determined from the stellar wind properties.